Life Style Factor Analysis and Body Mass Index (BMI) Of Semarang Runners - Dewi Surya Ningsih; Surjoputro, Antono; Syamsulhuda Budi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background:  Running has become one of the most popular sports for people of all ages. The presence of exciting running events and races has further boosted the sport’s popularity. However, enthusiasm for participating in running races is not always accompanied by a healthy lifestyle, including regular physical activity, adequate sleep, effective stress management, and balanced nutritional intake. Aims: This study aims to determine the factors influencing the BMI of the running community in Semarang City. Methods: The research employed a quantitative, cross-sectional design. The population consisted of members of the Semarang Runners community aged 18–24 years. A total of 71 respondents were selected using a total sampling method. Data were collected using the International Physical Activity Questionnaire (IPAQ), Pittsburgh Sleep Quality Index (PSQI), 24-hour food recall, Perceived Stress Scale (PSS), and BMI measurements. Data analysis was conducted using the chi-square test to assess correlations. Results: The results indicated that, based on the chi-square test, physical activity, sleep quality, stress, and achievement were not significantly associated with BMI, as their p-values were greater than 0.05. However, among dietary pattern variables—including energy, protein, fat, and fiber intake—only energy intake showed a significant association with BMI, with a p-value of 0.005. Conclusion: The study suggests that members of the Semarang Runners community should focus on managing their energy intake to support and improve their health. While other factors such as physical activity and sleep quality also contribute to overall fitness, energy intake appears to be a key determinant of BMI in this population.